Inventory of Healthcare Waste Generated at Kambia Government Hospital, Sierra Leone - Yahaya Kudush Kawa; Abubakarr Mohamed Kamara; Gibrilla Thullah; Hamidu David Mansaray (International Journal of Pollution: Prevention & Control, 2025)
This research studies the categories and management practices of healthcare waste generated at Kambia Government Hospital and stresses the need for effective waste management to protect health and the environment. The waste is categorized into seven types: general, infectious, pathogenic, pharmaceutical, sharps, chemical, and liquid. Weekly assessments discovered fluctuations in waste generation, with general and infectious waste consistently comprising significant portions. Notably, sharps waste underscored the risks associated with injury and contamination. Despite low chemical and liquid waste levels suggesting effective management, the hospital's overall waste management practices, including segregation, storage, collection, transportation, and disposal, reveal critical deficiencies. The lack of dedicated transport, functional incineration, and adequate staff training poses ongoing risks to safety and compliance with environmental standards.
Keywords: Segregation; Waste management; incinerator; infectious; pathological waste; sharps waste; waste disposal